Analytic Study for 66 kV Sub Transmission System Planning (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The objective of this paper is to know the operationconditions of the system in terms of power flow, power losses and the weak points of the network. After which, solutionswere proposed for solving such problems. The strategic andmethodology for planning Criteria are chosen in a way thatmatches the general standards. A seventeen years plan isconsidered with short and long term planning applied andcomputed, system model was designed and a simulation forthis model was performed using NEPLAN software. A strategicplan for the 17 year next for 66 kV sub-transmission networkhas been obtained. The targeted network consists of four ringsfed from four 220KV feeding points and capable of providingan expected total demand of 253 MW.